A ABSTRAK Indonesia salah satu negara yang rawan akan bencana alam seperti gempa bumi dan gunung api. Bencana-bencana alam tersebut bisa terjadi kapan saja dan dimana saja. Salah satu provinsi di Indonesia yang rawan akan letusan gunung api adalah Bali. Pen - Nia Maharani (PendIPA Journal of Science Education, 2023)
Indonesia is a country prone to natural disasters such as earthquakes and volcanoes. These natural disasters can happen anytime and anywhere. One of the provinces in Indonesia which is prone to volcanic eruptions is Bali. Adequate basic knowledge related to volcanoes is needed by all Balinese people, especially children, regarding anticipatory measures for volcanic eruptions. The goal is to reduce the risk of volcanic hazards. In this study, researchers took the research location at the Dharma Jati I Klungkung Bali orphanage. A number of questions in the form of a questionnaire were given to the children living in the orphanage. Based on previous observations, there was no counseling about volcanic disasters at the orphanage. Facilities and infrastructure are still limited to television so children get little information and some have never received any information at all. A questionnaire containing 10 questions was given to the orphanage children regarding basic knowledge of volcanoes such as the meaning, causes, characteristics and effects of volcanic eruptions with the result that the orphanage children still lack knowledge about the volcano itself.